Rebleeding and bleeding in the year following intracranial aneurysm coiling: analysis of a large prospective multicenter cohort of 1140 patients—Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) Study. (16th June 2020) - Pierot, Laurent; Barbe, Coralie; Herbreteau, Denis; Gauvrit, Jean-Yves; Januel, Anne-Christine; Bala, Fouzi; Ricolfi, Frédéric; Desal, Hubert; Velasco, Stéphane; Aggour, Mohamed; Chabert, Emmanuel; Sedat, Jacques; et al.
Abstract : Background: Endovascular treatment is the first line therapy for the management of ruptured and unruptured intracranial aneurysms, but delayed aneurysm rupture leading to bleeding/rebleeding can occur subsequently. ARETA (Analysis of Recanalization after Endovascular Treatment of intracranial Aneurysm) is a prospective, multicenter study conducted to analyze aneurysm recanalization. We analyzed delayed bleeding and rebleeding in this large cohort. Methods: 16 neurointerventional departments prospectively enrolled patients treated for ruptured and unruptured aneurysms between December 2013 and May 2015 (ClinicalTrials.gov: NCT01942512 ). Participant demographics, aneurysm characteristics and endovascular techniques were recorded. Data were analyzed from participants with ruptured or unruptured aneurysms treated by coiling or balloon-assisted coiling. Rates of bleeding and rebleeding were analyzed and associated factors were studied using univariable and multivariable analyses. Results: The bleeding rate was 0.0% in patients with unruptured aneurysms and 1.0% (95% CI 0.3% to 1.7%) in patients with ruptured aneurysms. In multivariate analysis, two factors were associated with rebleeding occurrence: incomplete aneurysm occlusion after initial treatment (2.0% in incomplete aneurysm occlusion vs 0.2% in complete aneurysm occlusion, OR 10.2, 95% CI 1.2 to 83.3; p=0.03) and dome-to-neck ratio (1.5±0.5 with rebleeding vs 2.2±0.9 without rebleeding, OR 0.2, 95% CI 0.04 to 0.8; p=0.03). Modalities of management of aneurysm rebleeding as well as clinical outcomes are described. Conclusions: Aneurysm coiling affords good protection against bleeding (for unruptured aneurysms) and rebleeding (for ruptured aneurysms) at 1 year with rates of 0.0% and 1.0%, respectively. Aneurysm occlusion and dome-to-neck ratio are the two factors that appear to play a role in the occurrence of rebleeding.